An Overview Profile and Green Purchasing Behavior of Consumers in the Northern Region of Malaysia - Sharaf, Muhammed Abdullah; Perumal, Selvan (Journal of Research in Marketing (ISSN: 2292-9355), 2018)
Green purchasing has been an important topic since the introduction of green products in the late 1980s which led in later years to a new market segment known as green consumers, and since then governments and rules regulators became part of this wave which encouraged the growth of green products. Therefore, this study aims to investigate an overview of profile of Malaysians and the level of green purchasing behavior. The paper reports and analyses the findings of 383 questionnaires which were collected from selected states in north Malaysia namely: Penang, Kedah and Perlis. The paper illustrates an overview consumer profile among Malaysians. Furthermore, the results show that green purchasing level among Malaysian is at a moderate level. Discussion and implication of this study are introduced in the last section of this paper.